Gliomas, germ cell tumors, and craniopharyngioma. (22nd September 2020) - Aridgides, Paul; Janssens, Geert O.; Braunstein, Steve; Campbell, Shauna; Poppe, Matthew; Murphy, Erin; MacDonald, Shannon; Ladra, Matthew; Alapetite, Claire; Haas‐Kogan, Daphne
Abstract: This report summarizes the current multimodality treatment approaches for children with low‐ and high‐grade gliomas, germinoma, and nongerminomatous germ cell tumors, and craniopharyngiomas used in the Children's Oncology Group (COG) and the International Society of Pediatric Oncology (SIOP). Treatment recommendations are provided in the context of historical approaches regarding the roles of surgery, radiation, and chemotherapy. Future research strategies for these tumors in both COG and SIOP are also discussed.